2020
DOI: 10.3390/f11060673
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Pine-Oak Glacial Refugia in the Mediterranean Basin: A Biogeographic Approach Based on Charcoal Analysis and Spatial Modelling

Abstract: During the glacial episodes of the Quaternary, European forests were restricted to small favourable spots, namely refugia, acting as biodiversity reservoirs. the Iberian, Italian and Balkan peninsulas have been considered as the main glacial refugia of trees in Europe. In this study, we estimate the composition of the last glacial forest in a coastal cave of the Cilento area (SW Italy) in seven time frames, spanning from the last Pleniglacial to the Late Glacial. Charcoal analyses were performed in seven archa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 84 publications
0
35
0
Order By: Relevance
“…Said software has been used in many fields of science which proved its validity [81][82][83][84][85], being widely recognized as the most used tool, even for small sample sizes and poorly known species' distributions [71]. The modelling process is able to indicate suitable conditions for species in areas where their presence has not been registered or evidenced; several studies supported the reliability of SDMs [67,86,87]. Since this process is iterative, the modelling outcomes can highlight other factors related to the physical environment, anthropogenic influences or conditions of growth and reproduction of the species [88][89][90].…”
Section: Species Distribution Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Said software has been used in many fields of science which proved its validity [81][82][83][84][85], being widely recognized as the most used tool, even for small sample sizes and poorly known species' distributions [71]. The modelling process is able to indicate suitable conditions for species in areas where their presence has not been registered or evidenced; several studies supported the reliability of SDMs [67,86,87]. Since this process is iterative, the modelling outcomes can highlight other factors related to the physical environment, anthropogenic influences or conditions of growth and reproduction of the species [88][89][90].…”
Section: Species Distribution Modelsmentioning
confidence: 99%
“…Hence, several models from different communities may be obtained, and thus their spatial-temporal dynamics In order to achieve higher accuracy in establishing the influence of bioclimatic scenarios, models of singular thermophilic and xerophilous species that coexist with M. europaea could be compared in equal space-time conditions [113]. Hence, several models from different communities may be obtained, and thus their spatial-temporal dynamics analyzed [86,87]. In addition, indirect gradient variables corresponding to the physical characteristics of the territory (elevation, orientation, slope, geology, etc.)…”
Section: Distribution Dynamicsmentioning
confidence: 99%
“…We found that the Jeju populations harbor a level of allele richness ( A R ) and private allele rate ( P riv ) comparable to those of Kyushu populations. Although, such indicators provide a strong possibility for the existence of refugia in this area [ 77 , 78 , 79 ], we are convinced that Jeju Island did not serve as the glacial refuge of Q. gilva . In agreement with our assumption, ENM showed that the probability values for the distribution of the trees on Jeju Island during the LGM converged at zero.…”
Section: Discussionmentioning
confidence: 99%
“…The maxent model ran 1, 000 iterations of the processes or set the value of threshold to 0.00001. Meanwhile, the Receiver Operating Characteristic plot, the Area Under Curve (AUC) values, and the True Skill Statistics (TSS) were used to measure the accuracy of the Maxent model [ 30 , 31 ]. The greater value of AUC represented the better performer [ 32 ].…”
Section: Methodsmentioning
confidence: 99%